Barriers Prevent EGP Teachers from Becoming ESP Practitioners in the Context of an Indonesian Tertiary Education - Suherman, Andri (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
It has been argued by scholars that ESP (English for Specific Purposes) has several absolute features which distinguish it from EGP (English for General Purposes). It is not surprising that many EGP teachers face difficulties when teaching ESP classes. This mixed-method study randomly recruited EGP teachers (N=50) to complete an online survey regarding barriers they have experienced in teaching ESP courses. Some of them (N=20) were then invited to participate in interview sessions to discover their strategies in breaking the barriers. The results from quantitative data in the online survey showed that the teachers have been dealing with five different barriers with Subject Knowledge being the most difficult barrier to handle (M=3.14, SD=0.86). Meanwhile, the qualitative findings from the interview process revealed several strategies employed by the teachers to break the barriers appeared to have been intercorrelated and affected to each other. As this finding revealed, university authorities need to provide EGP teachers with some supports (i.e. training programs, financial aid, and relevant textbooks) to minimize potential barriers when teaching ESP classes. Limitations and suggestions for future research are also presented.